Non-invasive Mechanic Ventilation During the "Weaning - Murat Ünsel; Perihan Ergin Özcan (Galenos Yayinevi, 2016)
SUMMARY Weaning of the patients from mechanical ventilation is a clinically important subject. Recently, applications of non-invasive mechanic ventilation (NIV) are increasing in post extubation respiratory failure. Studies show that NIV is effective in the weaning of chronic obstructive pulmonary disease, presenting with hypercapneic respiratory failure and in the attacks of other chronic respiratory failure, but efficacy and reliability in the other patient group is limited. NIV must be applied by the experienced team in the selected patient group.